Strategi Guru dalam Mengatasi Kesulitan Membaca Notasi Balok pada Pembelajaran Piano di Gittith Music School Boja - Michael Febriyan Setya Wibisono; Moh. Muttaqin (Lembaga Pengembangan Kinerja Dosen, 2026)
Music education requires literacy in reading staff notation, yet many piano students struggle to master it, particularly in non-formal institutions such as Gittith Music School Boja, which has not fully implemented notation-based learning standards. This study aims to analyze teachers’ strategies in overcoming students’ difficulties in reading staff notation during piano lessons at the institution. A descriptive qualitative approach with a case study method was employed, with data collected through observation, interviews, and documentation involving one piano teacher and several students. The findings show that students’ difficulties include note and finger-position reading, chromatic sign recognition, staccato and legato technique, and playing in fast tempo. The teacher addressed these difficulties through a combination of the drill method, gradual method, demonstration method, and individualized guidance tailored to each student’s ability. These strategies reflect the application of behaviorism theory through repeated practice and constructivism theory through gradual, experience-based learning. The findings imply the importance of a flexible, student-centered combination of teaching methods in non-formal music education to improve the effectiveness of learning staff notation reading.